2021
DOI: 10.1002/qua.26608
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic SiC: A potential anode material for Na‐ion battery with extremely high storage capacity

Abstract: Bulk SiC phases with tetrahedral arrangements have been identified several decades ago, and have been widely studied due to their potential applications. Until recently, Yaghoubi et al.'s experiment (Chem. Mater. 2018, 30, 7234) observed the existence of graphitic SiC with few SiC layers stacking, which implies the possible synthesis of such material in the future. In this work, we explored the potential application of graphitic SiC as the Na-ion battery anode via the first-principle simulation. Our results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Most forms of SiC are chemically bonded via a sp 3 -type hybridization and show a wide band gap semiconducting nature. Moreover, is the graphitic silicon carbide (1:1) predicted to be a semiconductor, , and even the graphene-like stable monolayer h SiC, with an alternating Si and C arrangement and sp 2 -type hybridization, shows an insulating band structure contrary to the Dirac cones found in pure graphene. Only the work by Qin et al has revealed a semimetal siligraphene monolayer with CC and SiSi bonds in a paired configuration in a 1:1 ratio of Si and C, which facilitate the reinstatement of the Dirac cone along the G-Y k -path .…”
Section: Introductionmentioning
confidence: 99%
“…Most forms of SiC are chemically bonded via a sp 3 -type hybridization and show a wide band gap semiconducting nature. Moreover, is the graphitic silicon carbide (1:1) predicted to be a semiconductor, , and even the graphene-like stable monolayer h SiC, with an alternating Si and C arrangement and sp 2 -type hybridization, shows an insulating band structure contrary to the Dirac cones found in pure graphene. Only the work by Qin et al has revealed a semimetal siligraphene monolayer with CC and SiSi bonds in a paired configuration in a 1:1 ratio of Si and C, which facilitate the reinstatement of the Dirac cone along the G-Y k -path .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, silicon, carbon, and SiC can show different properties and functionalities useful for various applications depending on their dimensions [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. For example, in our previous work [ 20 ], we reported the synthesis of graphene foam and three-dimensional graphene composites that showed remarkable electrochemical and mechanical properties when used for supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%